Plantas de cobertura como provedora de nitrogênio e adubação nitrogenada na cultura do milho - Freitas, Leandro Alves (2020)
The maintenance of residues and the minimum disturbance on the soil surface, combined with the use of crop rotation are basic premises for a soil conservation system, whose management of areas without the adoption of these concepts contributes to the loss of soil quality. The study evaluated the use of summer cover crops, with quantification of biomass production, N cycling, as well as the effects on the agronomic parameters of corn grown with and without nitrogen fertilization. The research was conducted in an experimental area at the Federal Technological University of Paraná (UTFPR), Câmpus Dois Vizinhos, in an Red Oxisol with a very clayey texture. The experimental design is presented in randomized blocks in a factorial scheme (8x2), and three replications, composed of seven species of summer cover crops, and a fallow area, with and without nitrogen cover fertilization in the corn crop. In order to maintain the N in the system, the NF was sown after the summer cover plants. The evaluations in the cover and NF plants were of biomass production, accumulation of total N and C, the rate of decomposition and release of N. In addition, the responses of the production components of the corn crop were measured, as well as the accumulation of C and N. The remaining dry mass and N release were evaluated during 180 days for summer cover plants and 90 days for NF using decomposition bags (Litter bags). The results were submitted to non-linear regression models, while the effect of cover crops and nitrogen fertilization on corn production components, as well as on the accumulation of C and N in biomass and corn grains was compared by Scott test Knott. The remaining dry matter dynamics of the cover plants presented a fast initial phase followed by a slower one. At 15 days after the allocation of Litter bags (DAA), there were the smallest remaining dry masses for Jack beans, Lab-lab and Showy ratllebox in 2018, the following year the same occurred for Jack beans and Showy ratllebox. Likewise, the NF provided the lowest dry matter remaining at 30 days after allocation in 2018. Over the period of 120 DAA, the time of greatest N extraction in the corn crop, the Jack beans added to the subsequent NF released levels of N in quantities close to nitrogen cover fertilization. The remaining N followed the same pattern for remaining dry matter and N release, with the lowest amounts being obtained in the first 15 DAA, for all systems with cover plants. The highest yields of DM, as well as accumulation C and N were obtained for the jack bean, which allowed greater amounts of dry matter remaining, in addition to the greater accumulated and released values of N, which together with the subsequent NF enabled the amount of availability from N to levels similar to nitrogen cover fertilization. Jack beans and gray and black mucunas showed greater synchrony of N release and availability at the time of greater demand for maize culture, were also the systems that expressed availability of N equivalent to fertilized systems, resulting in minimal differences between the components of production and accumulation of N in corn. The analysis of main components indicated that the adoption of cover crops attributed positive values to the corn production components in the two years of evaluation, in addition to the fallow systems showing negative values for these components.